Digit ratio (2D:4D) and physical fitness in early adolescence: A potential criterion for talent identification? - Avcu, Emsal Çağla; Yaşar, Ali Emre; Cinar, Vedat (My University, 2025)
A low digit ratio (2D:4D), as an indicator of prenatal androgen exposure, is assumed to be associated with higher physical fitness and athletic performance. This study aims to examine the relationship between the 2D:4D and certain physical fitness components during early adolescence. The study was conducted as a cross-sectional research. Early adolescents without any prior sports background voluntarily participated in the study. In the study, the participants’ right and left hand 2D:4D were measured, and their physical fitness was assessed using tests for handgrip strength, flexibility, agility, speed and power performance. The findings indicated that there was no significant correlation between the 2D:4D and all of the physical fitness components involved in this study in both female and male participants. In the gender-based evaluation, it was determined that the 2D:4D was higher in females. The results show that the 2D:4D is not significantly correlated with handgrip strength, flexibility, agility, speed and power performance in individuals without any prior sports background during early adolescence. In this context, the use of the 2D:4D as a potential biological indicator for talent selection was not supported in this age group and sample.
Keywords: Physical fitness; physical performance; Early adolescent; sports ability.